A bridge safety monitoring system for prestressed composite box-girder bridges with corrugated steel webs based on in-situ loading experiments and a long-term monitoring database. (1st November 2016) - Sung, Yu-Chi; Lin, Tzu-Kang; Chiu, Yi-Tsung; Chang, Kuo-Chun; Chen, Kuo-Long; Chang, Chung-Ching
Highlights: Forced vibration and in-situ static loading experiments were carried out before service. Good agreement between the numerical model and the in-situ experiment data. The warning and critical thresholds enables effective judgment for management agencies. Inclination angles prediction for the 50-year life cycle supports the long-term safety. Abstract: In order to reduce the self-weight of Highway No. 4 in the Taichung living circle in Taiwan, a corrugated steel web, with a span of 145 m, is used to replace the conventional concrete web. To appraise the structural safety and operating conditions of a prestressed composite box-girder bridge with a corrugated steel web, which is the first bridge of its kind in Taiwan, a bridge monitoring system is developed based on in-situ experiments, numerical modeling, and long-term monitoring. In order to determine the initial static and dynamic behaviors of a real bridge, a series of experiments are first carried out on a newly-constructed bridge. Before entering service, a bridge is subjected to forced vibration experiments and static loading experiments to establish its initial condition. In this study, a numerical model of the bridge is constructed based on the finite element method. The results of the structural analysis are compared with experimental data, and the two sets of results are found to show good agreement. Moreover, thermometers, strain gages, displacement gages, and inclinometers are installed on the bridge to measure changes in the physical quantities, and the monitored temperature gradient profile over a year is fed back to the numerical model for further analysis. Results have indicated that the in-situ linear variable differential transformer (LVDT) and inclinometer monitoring data can be effectively simulated by the numerical model. Finally, based on the material properties, numerical model, and long-term monitoring data from inclinometers, the safety threshold of the bridge is determined to provide a useful reference for bridge management agencies. Prediction of the extreme inclination angles by the Generalized Extreme Value Distribution (GEVD) method for the 50-year life cycle of the monitored bridge also falls within the envelopes of the warning and critical thresholds, which support the long-term safety of bridges.